Bimbingan Teknis Microsoft 365 bagi Tenaga Kependidikan di Lingkungan FKIP UNTAN - Dwija Saptahadi; Andang Firmansyah; Helen Sasty Pratiwi; Subarjo Subarjo; Ratih Rahmahwati; Hemri Yansa (Institut Agama Islam Negeri Bengkulu, 2023)
To help improve Institutional accreditation and make equipment spending efficient, using Microsoft Office 365 is the right solution for FKIP UNTAN, which has changed its status to become a Public Service Agency (BLU) University. Service activities by maximizing the use of Microsoft Office 365 are considered activities that answer the institution's needs. The Microsoft Office 365 account provided by the team is a premium account with exclusive and premium features to make it easier and more effective for the work of education staff at FKIP UNTAN. This community service activity aims to maximize the Microsoft Office 365 account that UNTAN has provided. The result of this activity is that participants get premium Microsoft Office 365 accounts, gain knowledge about the features available in Microsoft Office 365 applications, and gain knowledge to maximize the use of existing features in Microsoft Office 365 applications.